Asimilasi Kultural Arab-Melayu Palembang - Apriana Apriana (Medina-te : Jurnal Studi Islam, 2019)
Palembang is a very plularis population, inhabited by various ethnic groups. The city is crossed by the Musi river channel which is one of its supporters. The diversity of the population has resulted in assimilation or assimilation between migrants and local residents. In this study examines Palembang Arabic-Malay Assimilation. The process of assimilation of Arabs and Malays in Palembang occurred at the time of the arrival of the Hadramaut colony to the archipelago, especially Palembang in the mid-16-17 century, most of them were men so it was not surprising that the Sayids needed women to fulfill their inner needs. Furthermore on the other hand the thing that is beneficial is that they are regarded as descendants and successors of the Prophet. Therefore, they get a high social position so they can easily marry noble women. With this marriage, that's when they can adopt the lifestyle, language and daily life of the Malay community. Palembang's Arabic-Malay kutural assimilation process in terms of the use of Malay, home architecture, food, clothing, ritual / ceremonial. The factors that influence the cultural assimilation of the Arab-Malay community in Palembang, namely supporting factors include: economic, religious, political, ethnicity and cultural factors. The inhibiting factors include: historical-political, economic, ideological and socio-cultural factors.